The Effect of Reinforcement Skills on Increasing the Learning Motivation of Grade XI Students in Christian Religious Education - Napitupulu, Khatarina; Munthe, Bangun; Siregar, Nurliani (CV Putra Publisher, 2025)
The purpose of this study is to see how the influence of skills to provide reinforcement on increasing the learning motivation of class XI students in Christian religious education subjects at SMK Negeri 11 Medan with a total of 35 people. This study uses a descriptive method, while the data analysis carried out by hypothesis research is the correlation of product moment person with the data collection tool being a questionnaire. From the results of the correlation test (r) 0.70 with a determination test of 49% and to determine the significance of the correlation coefficient at the real level (α) = 0.05, a